2021
DOI: 10.1016/j.jamda.2020.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Does Copper Prevent Nosocomial Transmission of COVID-19?

Abstract: This letter discusses the preventive efficacy of copper in nosocomial infections by SARS-CoV-2 and makes us question the importance of hand contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The results confirmed its high resilience in saliva, and proved its ability to remain active for long periods outside the body, even in hostile environmental conditions . Arguably, this peculiarity is responsible for the high level of contagion, since the harder shell protects the virion from inactivation …”
Section: Airborne Transmission Of Sars-cov-2supporting
confidence: 62%
See 2 more Smart Citations
“…The results confirmed its high resilience in saliva, and proved its ability to remain active for long periods outside the body, even in hostile environmental conditions . Arguably, this peculiarity is responsible for the high level of contagion, since the harder shell protects the virion from inactivation …”
Section: Airborne Transmission Of Sars-cov-2supporting
confidence: 62%
“… 70 Arguably, this peculiarity is responsible for the high level of contagion, since the harder shell protects the virion from inactivation. 71 …”
Section: Airborne Transmission Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…A non-randomised study found a 90% reduction in viral counts within six minutes and 99.5% in 11 minutes [100]. The effects of UV-C need more modeling particularly with attention to the effectiveness of decolonisation with distance from objects [101].There is evidence that copper surfaces reduce SARS-CoV-2 contamination levels [102][103][104][105][106][107].…”
Section: Increasing the Use Of Medical Or Surgical Masks And Hand Hygmentioning
confidence: 99%